2016
DOI: 10.1007/s11033-015-3936-0
|View full text |Cite
|
Sign up to set email alerts
|

EGCG ameliorates the hypoxia-induced apoptosis and osteogenic differentiation reduction of mesenchymal stem cells via upregulating miR-210

Abstract: The healing process of fractured bone is affected by the multiple factors regulating the growth and differentiation of osteoblasts and bone mesenchymal stem cells (MSCs), however, such markers and molecular events need to be orchestrated in details. This study investigated the effect of polyphenol(-)-epigallocatechin-3-gallate (EGCG) on the hypoxia-induced apoptosis and osteogenic differentiation of human bone marrow-derived MSCs, examined the miR-210 induction by EGCG, explored the target inhibition of the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…At the same concentration, EGCG can also decrease osteoclastogenesis via the regulation of osteoprotegrin (OPG) and the receptor activator of Nuclear factor-kB (RANK) ligand (RANKL) in pre-osteoclast feeder cells, ST2 [32]. Qiu's study also showed that 10-40 µmol/L of EGCG significantly inhibited hypoxia-induced apoptosis in BMSCs and increased the level of runt-related transcription factor 2 (Runx2), BMP-2, type I procollagen, and alkaline phosphatase activity [33]. We found No published data regarding the effect dose of EGCG on fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…At the same concentration, EGCG can also decrease osteoclastogenesis via the regulation of osteoprotegrin (OPG) and the receptor activator of Nuclear factor-kB (RANK) ligand (RANKL) in pre-osteoclast feeder cells, ST2 [32]. Qiu's study also showed that 10-40 µmol/L of EGCG significantly inhibited hypoxia-induced apoptosis in BMSCs and increased the level of runt-related transcription factor 2 (Runx2), BMP-2, type I procollagen, and alkaline phosphatase activity [33]. We found No published data regarding the effect dose of EGCG on fracture healing.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, miR‐210 might accelerate the malignant progression of OS through promoting the dedifferentiation of OS cells. There is evidence that miR‐210 promotes the osteoblastic differentiation of bone marrow mesenchymal stem cells by targeting activin A receptor type 1B (AcvR1b) and ephrin‐A3 (EFNA3) (Mizuno et al, ; Qiu et al, ). Based on our previous analysis of gene expression (GSE38135), there was no change in the expression of AcvR1b or EFNA3 during the dedifferentiation of OS (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the amount of polyphenols found in the yerba mate infusion are greater than its amount found in blended tea support this hypothesis (Heck & de Mejia, ). Epigallocatechin, which a high amount is also is found in green tea, has been showing a favorable effect on bone metabolism in experimental studies (Qiu et al, ). Moreover, subjects that have an intake of three or more cups per day of black tea were found to have fewer fractures than subjects with a lesser intake (Myers et al, ).…”
Section: Discussionmentioning
confidence: 99%